THE EFFECTIVENESS OF SOCIAL MEDIA MARKETING ON CONSUMER PURCHASE DECISIONS (International Journal of Food and Nutritional Sciences, 2022)
The rapid proliferation of social media platforms has transformed the landscape of marketing, providing businesses with novel avenues to engage with consumers. This study examines the effectiveness of social media marketing on consumer purchase decisions, highlighting how various social media strategies influence consumer behavior and drive sales. Through a comprehensive review of existing literature and empirical analysis, the research identifies key factors such as content quality, engagement levels, influencer impact, and social proof as critical determinants in the consumer decision-making process. The findings suggest that social media marketing significantly enhances brand visibility and credibility, thereby positively affecting consumer purchase intentions. High-quality, engaging content that resonates with the target audience and fosters interactive communication is particularly effective in converting potential customers into buyers. Influencers play a pivotal role by leveraging their credibility and reach to sway consumer opinions and behaviors. Additionally, the presence of social proof, such as user reviews and testimonials, further strengthens consumer trust and purchase likelihood. Businesses that strategically utilize social media marketing can effectively influence consumer purchase decisions. However, the dynamic and interactive nature of social media requires continuous adaptation and engagement to sustain consumer interest and loyalty. Future research should explore the long-term impact of social media marketing and the evolving consumer expectations in the digital age.